Elemen Kebudayaan dalam Pengajaran Bahasa Malaysia kepada Pelajar Asing di UTM: Persepsi Pelajar - Halimah Binti Maalip (Balai Bahasa Sumatera Utara, 2019)
In moving towards a world-class university Universiti Teknologi Malaysia (UTM) has taken a number of proactive measures. One of these measures is to increase the intake of foreign students. With the increasing number of students indirectly to the needs of teaching English to Foreign Students (BMPA) has also increased. BMPA can help students to socialize with local people, especially the poor knowledge of English. With such a plan designed for the systematic teaching materials to not only learn the rules of language alone but by paying attention to cultural elements. Accordingly a study conducted on students attending courses in English to know their perception of cultural elements that are applied in the teaching materials. This study used quantitative methods. A total of 114 respondents participated in the study. This study is a case study because only focus on one characteristic, namely foreign students from non-Malay country studying in Universiti Teknologi Malaysia (UTM). The findings of this study can view students' perceptions of teaching Bahasa Malaysia and cultural elements in the course. In a paper also discussed the implementation of teaching at UTM BMPA, which is a compulsory subject.